The Influence of Population Income Mobility on Inequality Change - БогомоловаТатьяна Юрьевна; ТапилинаВера Сергеевна; РостовцевПетр Симонович (Journal of Economic Sociology, 2010)
The paper presents the results of the investigation of causality between income changes and inequality change in their distributions in Russia in 1990s. Income mobility is seen as a mechanism of the inequality transformation in the income distribution. The authors determine the characteristics of inequality transformation and the type of inequality dynamics in Russia in 1994-1995, 1995-1996, 1996-1998.